Defect Control in the Synthesis of 2 D MoS2 Nanosheets: Polysulfide Trapping in Composite Sulfur Cathodes for Li–S Batteries. Issue 6 (19th December 2019) - Abraham, Alyson; Wang, Lei; Quilty, Calvin D.; Lutz, Diana M.; McCarthy, Alison H.; Tang, Christopher R.; Dunkin, Mikaela R.; Housel, Lisa M.; Takeuchi, Esther S.; Marschilok, Amy C.; Takeuchi, Kenneth J.
Abstract: One of the inherent challenges with Li–S batteries is polysulfide dissolution, in which soluble polysulfide species can contribute to the active material loss from the cathode and undergo shuttling reactions inhibiting the ability to effectively charge the battery. Prior theoretical studies have proposed the possible benefit of defective 2 D MoS2 materials as polysulfide trapping agents. Herein the synthesis and thorough characterization of hydrothermally prepared MoS2 nanosheets that vary in layer number, morphology, lateral size, and defect content are reported. The materials were incorporated into composite sulfur‐based cathodes and studied in Li–S batteries with environmentally benign ether‐based electrolytes. Through directed synthesis of the MoS2 additive, the relationship between synthetically induced defects in 2 D MoS2 materials and resultant electrochemistry was elucidated and described. Abstract : Controlled additives : Hydrothermally prepared MoS2 nanosheets that vary in layer number, morphology, lateral size, and defect content are synthesized and thoroughly characterized. These findings highlight the importance of synthetic control and morphological tuning of material additives.